An observational study of player behaviours under varying task constraints in professional Australian football players - Tribolet, R.; Sheehan, W. B.; Novak, A. R.; Watsford, M. L.; Fransen, J. (International Journal of Sports Science & Coaching, 2024)
An evaluation of player behaviour and performance across different playing conditions in team sport is difficult. This study examined integrative (indegree and outdegree importance) and individual (goals, kicks, handballs, marks, tackles, kick and handball proficiency) level behaviours at one professional Australian Football club across three different conditions: small-sided games (SSGs), match simulation and competitive Australian Football League (AFL) matches. Estimated marginal means identified negligible changes for integrative measures across conditions. This may suggest larger changes to control parameters are required to modify these behaviours, as it relies on interdependent cooperative behaviour. Individual level behaviours demonstrated varied responses across changing conditions. AFL matches revealed the lowest kicks and marks per minute compared to the other conditions, whilst having the highest rate of tackles. Players had lower kick proficiency in conditions with a higher number of players. Moreover, one SSG with a floater (player who participates in attack for both teams) elicited a higher number of handballs per minute relative to every other condition. These findings provide implications for measuring the (in)stability of individual and integrative level behaviours and how changes to constraints may alter these metrics. This method may provide a foundation for future hypotheses testing and for player monitoring that can assist practitioners to examine the changes in players behaviours in response to changing constraints.